Model Strategi Pengembangan Positioning Kafe di Surabaya - Arasy Alimudin (BISMA (Bisnis dan Manajemen), 2018)
The purpose of this research is to know and build café position, the method used is descriptive quantitative by collecting consumer perception and based on approach to consumer and based on condition of current situation and condition. The positioning of Jumbo Juice cafe compared to its main competitor is done by frequency distribution analysis technique. The results showed that the strategy model for the development of Jumbo Juice cafe positioning in Surabaya was; Promotion of café location by giving direct appointment of cafe existence very clear and easy to see around cafe environment. The custodian must keep the very cheap price offered to form a strong image among the cafe's consumers. Provide a full menu and a menu of new dishes not shared by competitor cafes. Improving service quality should be sustainable. Toilet facilities should be kept clean, safe and adequate parking. Sauna cafe must be developed so it will create a different susana with other competing cafes. And provide a sense of security to the cafe's visitors.